EVALUATION ANALYSIS OF SAMOSIR REGENCY GOVERNMENT PERFORMANCE EVALUATION VIEWED FROM FINANCIAL REPORT INFORMATION - Talenta Emma Marbun; Santy Aji Sitohang; Sahala Purba (Kajian Akuntansi, 2023)
This research aims to evaluate the financial performance of regional governments at several levels, including Regional Financial Autonomy Level, Fiscal Decentralization Level, PAD Effectiveness Level, PAD Efficiency Level, Regional Fiscal Effectiveness Level, Regional Fiscal Efficiency Level, and BUMD Contribution Level. This quantitative descriptive study examines the regional financial statistics of Samosir Regency from 2013 to 2020. Economic scale analysis is the data analysis method used. The findings show that the average value of Financial Autonomy Level is still meagre (6.93%); The level of Regional Financial Dependency is very high (91.65); The level of Fiscal Decentralization (6.30%) is deficient; PAD has an effectiveness rating of very effective (100.74%); 0.78% shows that PAD efficiency is very efficient. 115.41% is fiscal effectiveness; regional fiscal efficiency is quite effective (3.36%); the BUMD contribution of 6.40% is minimal. Keywords    : Financial Performance, District Government, financial Information.